EVALUATION OF EFFICACY AND SAFETY OF AZITHROMYCIN AND DOXYCYCLINE IN TREATMENT OF ACNE VULGARIS WITH DIFFERENT LEVELS OF SERUM TESTOSTERONE: A PROSPECTIVE, RANDOMIZED, CONTROLLED, COST-EFFECTIVE, COMPARATIVE STUDY - PADMAJA MEKALA; ROOPALI SOMANI; USHARANI PINGALI; VIJAYALAKSHMI SRIPATHI PANDITHARADHYULA; IMRAN KHAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of this study are to compare the therapeutic efficacy, safety, quality of life (QoL), and cost-effectiveness of azithromycin and doxycycline in patients with acne vulgaris and the correlation of serum testosterone levels with the severity of acne. Methods: A prospective, randomized, open-label study was conducted at a tertiary care hospital in South India, according to the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use Guideline for Good Clinical Practice principles. After institutional ethics committee approval, 100 patients aged 15–40 with moderate-to-severe acne were enrolled, excluding those with a history of gastritis, drug hypersensitivity, pregnancy, or under 12 years old. Participants were randomized to receive either oral azithromycin 500 mg daily for three consecutive days each week for 4 weeks, or doxycycline 100 mg daily for 28 days, along with topical treatments. Efficacy was measured by the type and number of acne lesions, graded according to standardized criteria. QoL was assessed using the Cardiff Acne Disability Index (CADI). Serum testosterone levels were correlated with acne severity. Results: Of the 96 patients (42 males, 54 females) who completed the study, 49 were in the azithromycin group and 47 in the doxycycline group. The mean age was 23.5 years in the azithromycin group and 22.1 years in the doxycycline group. Significant reductions in acne severity and number of lesions were observed in both groups (p<0.0001), with azithromycin showing superior improvement (p<0.01). At baseline, most patients had Grade 3 or 4 acne, which improved significantly post-treatment. QoL improvements were also significant in both groups, with mean CADI scores reducing from around 8 to below 4 (p<0.0001). A weak positive correlation (r=0.24) was found between serum testosterone levels and acne severity. Adverse events were mild and did not necessitate discontinuation. To achieve a 1 unit decrease in CADI, azithromycin treatment costed an additional rupees of 264.5 over doxycycline. Conclusion: Azithromycin and doxycycline are effective treatments for moderate-to-severe acne vulgaris, with significant improvements in clinical and QoL outcomes. While azithromycin offers better clinical efficacy, doxycycline provides a more cost-effective option. Further studies could explore long-term outcomes and the impact of hormonal variations on treatment efficacy.